2018
DOI: 10.17586/2220-8054-2018-9-4-568-572
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of core-shell nanocrystals obtained via dehydration of coprecipitated hydroxides at hydrothermal conditions

Abstract: Here, we propose a formation mechanism for core-shell nanoparticles by self-organization in coprecipitated mixed hydroxides under hydrothermal conditions. A thermodynamic reason for this process is because of a decrease in the components' solubilities together with an increase of structure's dimension. As a particular example of such type of behavior, we investigate core-shell nanoparticle formation in the ZrO 2-Y 2 O 3-H 2 O system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
(35 reference statements)
1
12
0
Order By: Relevance
“…As SCS oxide nanoparticles are prone to aggregation, their structure and dimensions should be studied by a complex of methods [215]. The studies in [157,158,161,162,169,197,198,212,216] showed the necessity to use such methods as the x-ray diffraction, line broadening analysis, small-angle x-ray and neutron scattering, transmission electron microscopy, low-temperature gas adsorption curve analysis, etc.…”
Section: Oxide Materials Production By Scsmentioning
confidence: 99%
“…As SCS oxide nanoparticles are prone to aggregation, their structure and dimensions should be studied by a complex of methods [215]. The studies in [157,158,161,162,169,197,198,212,216] showed the necessity to use such methods as the x-ray diffraction, line broadening analysis, small-angle x-ray and neutron scattering, transmission electron microscopy, low-temperature gas adsorption curve analysis, etc.…”
Section: Oxide Materials Production By Scsmentioning
confidence: 99%
“…As a rule, the conditions of hydrothermal synthesis (HTS), significantly affect the composition, structure, and size of particles and crystallites of the synthesized products [1][2][3][4][5][6][7]. Important factors in this case are the sequence and rate of reagents mixing and the pH of the hydrothermal fluid [8,9]. Changes in pH usually significantly affect the state and composition of phases resulting from hydrothermal treatment [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…A significant advantage of ZrO 2 material is its ability to be doped with yttrium oxide (Y 2 O 3 ), which allows one to vary the optoelectronic characteristics of ZrO 2 -Y 2 O 3 -based nanostructured systems. Doping with rare-earth metals or niobium (Nb) allows to significantly improve the transport characteristics of the photoelectode and to increase the PCE of the PSCs [12,13]. Previously reports of PSCs fabricated using undoped ZrO 2 -based photoelectode have been made [14].…”
Section: Introductionmentioning
confidence: 99%